Principles of international criminal law - Werle, Gerhard, author (The Hague : TMC Asser Press, 2009)
First edition published in 2005 by same publisher.
I. Foundations. Historical evolution of international criminal law -- Concepts, tasks and legitimacy -- International criminal law and the international legal order -- Sources and interpretation -- Universal jurisdiction, the duty to prosecute, transitional justice -- Enforcement -- Domestic implementation -- II. General principles. Towards a general theory of crimes under international law -- Material elements -- Mental element -- Individual criminal responsibility -- Superior responsibility -- Grounds for excluding criminal responsibility -- Inchoate crimes -- Omissions -- Official capacity and immunity -- Multiplicity of offenses -- Requirements for prosecution -- III. Genocide. Introduction -- Material elements -- Mental element -- Incitement to commit genocide -- Multiplicity of offenses -- IV. Crimes against humanity. Introduction -- Contextual element (attack on a civilian population) -- Individual acts -- Multiplicity of offenses -- V. War crimes. Introduction -- Overall requirements -- War crimes against persons -- War crimes against property and other rights -- Employing prohibited methods of warfare -- Use of prohibited means of warfare -- War crimes against humanitarian operations -- Multiplicity of offenses -- VI. The crime of aggression. The prohibition of aggression under international law -- Criminal responsibility under customary international law (war of aggression) -- The crime of aggression in the ICC statute : prospects.
Includes bibliographical references and index
Keywords: Criminal procedure (International law); Criminal law -- International unification